A Descriptive Analysis of End-of-Life Conversations With Long-Term Glioblastoma Survivors. (May 2018) - Miranda, Stephen P.; Bernacki, Rachelle E.; Paladino, Joanna M.; Norden, Andrew D.; Kavanagh, Jane E.; Palmor, Marissa C.; Block, Susan D.
Background: Early, high-quality serious illness (SI) conversations are critical for patients with glioblastoma (GBM) but are often mistimed or mishandled. Objective: To describe the prevalence, timing, and quality of documented SI conversations and evaluate their focus on patient goals/priorities. Design/Participants: Thirty-three patients with GBM enrolled in the control group of a randomized controlled trial of a communication intervention and were followed for 2 years or until death. At baseline, all patients answered a validated question about preferences for life-extending versus comfort-focused care and completed a Life Priorities Survey about their goals/priorities. In this secondary analysis, retrospective chart review was performed for 18 patients with GBM who died. Documented SI conversations were systematically identified and evaluated using a codebook reflecting 4 domains: prognosis, goals/priorities, end-of-life planning, and life-sustaining treatments. Patient goals/priorities were compared to documentation. Measurements/Results: At baseline, 16 of 24 patients preferred life-extending care. In the Life Priorities Survey, goals/priorities most frequently ranked among the top 3 were "Live as long as possible, " "Be mentally aware, " "Provide support for family, " "Be independent, " and "Be at peace." Fifteen of 18 patients had at least 1 documented SI conversation (range: 1-4). Median timing of the first documented SI conversation was 84 days before death (range: 29-231; interquartile range: 46-119). Fifteen patients had documentation about end-of-life planning, with "hospice" and "palliative care" most frequently documented. Five of 18 patients had documentation about their goals. Conclusion: Patients with GBM had multiple goals/priorities with potential treatment implications, but documentation showed SI conversations occurred relatively late and infrequently reflected patient goals/priorities.